Photoelectrochemical solar cells using [(dcbH2)2RuLL ], L,L′ = substituted pyridines, as nanocrystalline TiO2 sensitizers - Christian Graziani Garcia; Neyde Yukie Murakami Iha (International Journal of Photoenergy)
The development of thin-layer transparent solar cells based on dye sensitization of nanocrystalline n-type TiO2 undertaken at the Laboratory of Inorganic Photochemistry and Energy Conversion at the Chemistry Institute of Universidade de São Paulo is presented. Compounds of the formula cis- [(dcbH2)2RuLL ], L,L′ = substituted pyridines, as nanocrystalline TiO2, dcbH2=4,4′−(CO2H)2−2,2′-bipyridine and L,L′ = substituted pyridines, have been successfully employed as molecular sensitizers in photoelectrochemical solar cells based on dye-sensitization of n-TiO2. This regenerative solar cell consists of a TCO glass with a dye-sensitized TiO2 semiconductor film as a photoanode, I2/LiI solution in acetonitrile as a redox mediator and a transparent Pt coated TCO glass as a counter electrode. Efficient conversion of visible light into electricity was achieved with IPCE (Incident Photon-to-Current Conversion Efficiency) as high as 50% between 400 and 550 nm.